1986
DOI: 10.5962/bhl.title.60680
|View full text |Cite
|
Sign up to set email alerts
|

A systematic study of the nearctic larvae of the Hydropsyche morosa group (Trichoptera : Hydropsychidae) /

Abstract: A system of taxonomic characters based on primary and secondary setae is developed and applied to identification of larvae of the Hydropsyche Mosely. Of the Nearctic species known in the morosa group. H. abella Denning, andersoni Denning, cora Denning, dorata Denning, intrica Denning, protis Ross, and vanaca Denning remain unassociated in the larval stage, although diagnoses for three unnamed species known only as larvae are also provided. Secondary setal types are defined and illustrated, and a key is provide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

1992
1992
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 4 publications
0
26
0
Order By: Relevance
“…However, these larval characters have been shown to be highly variable within Hydropsyche species [22,23]. This is also evident in Churchill specimens (Figure 3B-C).…”
Section: Resultsmentioning
confidence: 78%
“…However, these larval characters have been shown to be highly variable within Hydropsyche species [22,23]. This is also evident in Churchill specimens (Figure 3B-C).…”
Section: Resultsmentioning
confidence: 78%
“…Invertebrate identifications followed keys in Ross (1944), Burks (1953), Flowers & Hilsenhoff (1975), Pescador & Berner (1981), Schefter & Wiggins (1986), Merritt & Cummins (1996), Wiggins (2000), Smith (2001), and Thorp & Covich (2001). Diet records used to generate a priori predictions of trophic status were published by Merritt & Cummins (1996), Benke & Wallace (1997), Wiggins (2000), Smith (2001), and Thorp & Covich (2001).…”
Section: Methodsmentioning
confidence: 98%
“…The Hydropsyche species are divided into groups according to the authors' indications on their longitudinal distribution. HW: maximum head-width of larvae of fifth instar, from data of Schuster and Etnier (1978) and Schefter and Wiggins (1986) for A, and Edington and Hildrew (1981) No field study appears to have examined the microdistribution of large-river species in Europe in relation to current velocity. In North America, two species, abundant in large rivers, have been studied: H. incommoda Hagen (as H. orris) abundant in the Upper Mississippi near Keokuk (Fremling 1960) and in the lower reach of the Savannah River (Gordon andWallace 1975, Cudney andWallace 1980), and H. rossi Cudney and Wallace (1980) reported that the biomass of H. incommoda was greatest at 25-50 cm/s over a range of 10-75 cm/s.…”
Section: Studies In Field Conditionsmentioning
confidence: 98%
“…Velocity was measured 2 mm above the rock surface, beside each retreat. Maximum density was at 20.6 cm/s for H. cockerelli Banks, a species living in the middle reaches of western montane streams (Schefter and Wiggins 1986), 16 cm/s for H. oslari Banks, which occurs mostly in the middle reaches of streams and small rivers (Schefter and Wiggins 1986) and 8.3 cm/s for H. occidentalis Banks. However, when velocity was measured 10 mm above the substrate, specific preferences were less distinct (28, 23, 22 cm/s, respectively) although they showed the same trend.…”
Section: Studies In Field Conditionsmentioning
confidence: 99%